Management of Soil as a Natural Resource in the Savinjska Statistical Region - Petauer, Milena (Journal for Geography, 2010)
Animals, plants and microorganisms could not exist without soil, because without it life on Earth would not be possible. Thus we should always be concerned with preserving the soil condition. This should be a personal, a municipal, as well as a national concern. Nevertheless, the role of soil is not sufficiently incorporated into the planning of sustainable development of the Savinjska statistical region, therefore more active approaches are needed in the field of soil management and protection (education, research, raising public awareness, soil protection programs, soil related educational excursions, etc.).